Analysis of Front Roll Movement In Gymnastics: An Inquiry Approach Among Physical Education Students - Wardhani, Rio; Arifin, Zainal (Physical Activity Journal (PAJU), 2024)
This study describes the analysis of front roll movement skills in students using an inquiry approach, emphasizing active exploration and investigation by students. The research method utilized was quantitative descriptive. The research sample consisted of 63 physical education students from IKIP PGRI Pontianak. The research results indicate that students' activity in performing front roll movements in gymnastics with the inquiry method showed improvement. Initial data showed that for Morning Class A, 19 students, or 63.3% out of 30 students, obtained a Poor Category; for Afternoon Class, 24 students, or 80% out of 30 students, obtained a Poor Category. After implementing the inquiry method, there was an improvement in Morning Class students, with 24 students, or 80% out of 30 students achieving a Medium Category, and in Afternoon Class A, 28 students, or 93.3% out of 30 students achieving a Medium Category. This study concludes that using the inquiry method can enhance the skills of physical education students in performing front roll movements in gymnastics